CR radiation dose optimization strategies: clinical practice approach - Borlinhas, Filipa (2017)
In medical radiation exposures, namely in Computed Tomography (CT), there is an inverse relationship between the image noise and radiation dose. Radiographers need to recognize the situations that require optimization and to apply optimization strategies, without compromise patient diagnosis. The purpose of this work, based on a literature review and on the analysis of routine CT procedures, is to provide an overview of CT optimization techniques feasible to implement in routine practice. The key parameters and the main situations that affect image quality and patient dose will be discussed. Several CT parameters can be adjusted such as potential and tube current, rotation time, Automatic Exposure Control (AEC), detectors configuration, slice thickness, Pitch, table speed, post-processing with the filter kernels, and so on. These parameters vary with patient anatomical region of interest, examination length, positioning, clinical information, and acquisition phases. Furthermore, there are new reconstruction algorithms developed by manufacturers that also help to optimize dose by reducing artifacts and image noise, and many studies state their superior results. Also, the knowledge on the CT parameters trade-offs between radiation dose and image quality is essential for dose optimization, so this will also be highlighted and described in this work. The solution for the excess of radiation dose problem is not only to reduce radiation dose in general but also to adequate and personalize this optimization to each patient and clinical situation. The literature points out some solutions to handle this problem and is very important that the Radiographers are familiar with those when performing CT examinations in practice.